Impact of dose-capping chemotherapy in concurrent chemoradiotherapy in rectal cancer patients. (October 2021) - Yang, Ran; Younis, Moftah; Joseph, Kurian; Ghosh, Sunita; Nijjar, Tirath; Severin, Diane; Tankel, Keith; Tamhane, Yash; Fairchild, Alysa; Spratlin, Jennifer; Mulder, Karen; Usmani, Nawaid
Introduction: The study evaluated the effect of chemotherapy dose-capping on disease recurrence, toxicity and survival of rectal cancer patients treated with chemoradiotherapy (CRT). Methods: 601 consecutive rectal cancer patients treated with concurrent CRT were retrospectively analysed. Dose-capped patients were defined as having a body surface area (BSA) ≥2.0 m 2 and who received <95% full weight-based chemotherapy dose. Binary logistic regression was used to study the factors associated with the outcome variables (capped vs. uncapped). Kaplan-Meier estimation evaluated significant predictors of survival. Results: The median follow-up time was 7.54 years. The rate of disease recurrence was significantly higher in dose-capped patients (35%) compared to those without dose-capping (24%, P = 0.016). The adjusted odds ratio for dose-capped patients experiencing recurrence was 1.64 compared to uncapped patients (95% CI, 1.10–2.43). Overall, dose-capped patients were less likely to experience significant toxicity requiring dose reduction and/or treatment break when compared to uncapped patients (15% and 28% respectively, P = 0.008).There was significant differences in PFS between capped and uncapped group (77% vs. 85%; P = 0.017). The 5-year OS in the capped group was 75.0%, and 80% in the uncapped group ( P = 0.149). Conclusions: Rectal cancer patients treated with dose-capped CRT were at increased risk of disease recurrence. Patients dosed by actual BSA did experience excessive toxicity compared to dose-capped group. We recommend that chemotherapy dose-capping based on BSA should not be practiced in rectal cancer patients undergoing CRT.